2016
DOI: 10.1111/dom.12706
|View full text |Cite
|
Sign up to set email alerts
|

Feedback suppression of meal‐induced glucagon‐like peptide‐1 (GLP‐1) secretion mediated through elevations in intact GLP‐1 caused by dipeptidyl peptidase‐4 inhibition: a randomized, prospective comparison of sitagliptin and vildagliptin treatment

Abstract: Vildagliptin and sitagliptin affected incretin hormones, glucose concentrations, insulin and glucagon secretion in a similar manner. Inter-individual variations in L-cell feedback inhibition may indicate heterogeneity in the clinical response to DPP-4 inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
10
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
(41 reference statements)
13
10
2
Order By: Relevance
“…A recent study from our group studying similar patients on metformin and using a similar meal challenge found intact and total GLP‐1 and GIP concentrations very similar to those observed in the present study (Table S4, Appendix S1) . Nevertheless, in the absence of a GLP‐1 receptor agonist, sitagliptin induced a more obvious reduction in plasma glucose than observed in the present study, i.e. on a background of metformin and liraglutide.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent study from our group studying similar patients on metformin and using a similar meal challenge found intact and total GLP‐1 and GIP concentrations very similar to those observed in the present study (Table S4, Appendix S1) . Nevertheless, in the absence of a GLP‐1 receptor agonist, sitagliptin induced a more obvious reduction in plasma glucose than observed in the present study, i.e. on a background of metformin and liraglutide.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies of sufficient sample size have clearly shown reductions in post‐meal glycaemic excursions with DPP‐4 inhibitor treatment in participants not receiving treatment with a GLP‐1 receptor agonist . A recent study from our group studying similar patients on metformin and using a similar meal challenge found intact and total GLP‐1 and GIP concentrations very similar to those observed in the present study (Table S4, Appendix S1) . Nevertheless, in the absence of a GLP‐1 receptor agonist, sitagliptin induced a more obvious reduction in plasma glucose than observed in the present study, i.e.…”
Section: Discussionsupporting
confidence: 85%
“…This is probably a feedback inhibition by the incretin hormone of their own secretion from K‐ and L‐cells. This has previously been suggested for GIP and GLP‐1 . The current study shows this feedback inhibition after each meal during a whole day.…”
Section: Discussionsupporting
confidence: 85%
“…This confirms a previous report on the effect of sitagliptin on total GIP levels after meal ingestion in healthy subjects and in patients with type 2 diabetes . Also, 2 other studies have shown a trend for a feedback inhibition by DPP‐4 inhibition on GIP secretion in type 2 diabetes, although of lesser magnitude than feedback inhibition of GLP‐1 secretion . These results are at variance with another previous study and further studies are warranted.…”
Section: Discussionsupporting
confidence: 89%
“…This measurement involves both the intact and degraded products of the hormones, and therefore reflects the total secretion of the hormones . The secretion of GLP‐1 has been demonstrated previously to be reduced by DPP‐4 inhibition, which is explained by a feedback inhibition by intact GLP‐1 on GLP‐1 secretion . We confirm this feedback in the present study as the concentrations of total GLP‐1 were lower after sitagliptin than after placebo during the clamp procedure and after the lunch meal, with a trend also after the breakfast meal.…”
Section: Discussionsupporting
confidence: 89%